Inflammatory Response, a Key Pathophysiological Mechanism of Obesity-Induced Depression - Shu-Lin Shao; Da-Qian Liu; Bo Zhang; Shu-Ming Huang (Mediators of Inflammation)
In recent years, with the acceleration of life rhythm and the increase of social competition, the incidence of obesity and depression has been increasing, which has seriously affected the quality of life and health of people. Obesity and depression, two seemingly unrelated physical and psychological diseases, in fact, are closely related: obese people are more likely to have depression than nonobese ones. We have reviewed and analyzed the relevant research literature and found that the inflammatory response plays a key role in obesity-induced depression. This article will discuss in detail the inflammatory mechanisms by which obesity induces depression.